Exploring Strategic Management Choices to Mitigate Climate Change Effects - Srinivasan, Rajesh (Digital Repository of Theses - SSBM Geneva, 2025)
India has a legitimate cause for worry over climate change, given that a substantial portion of its people relies on climate-sensitive industries such as agriculture, forestry, and fishing for their means of subsistence. Climate change will exacerbate the strain on natural and social systems that are already under significant pressure as a result of increasing industrialization, urbanization, and economic expansion. The study aims to consolidate limited and dispersed literature and data on "Climate Change" and "Agriculture Growth" in order to provide a comprehensive understanding of the significant issue of climate change in India. In this study, the methodology is a systematic approach used to determine the outcome of a particular problem related to a certain subject or issue. The framework describes the details of indicators of environmental degradation, climate change and Agriculture Growth along with data items, geographical unit of collection of data, periodicity, sources of data and metadata linkage. In result, the data set includes data spanning 35 years (1990-2024), with significant variability in key environmental and socio-economic indicators. CO2 emissions range from 300 to 620 Mt, averaging 460 Mt with a standard deviation of 101.71, indicating moderate variability. CO2, CH4, and N2O Emissions all have extremely high correlations with Year, Agricultural Output, Energy Consumption, and Urbanization Rate (close to 1.000), indicating consistent increases over time and a close relationship with industrial activity and urban growth. The average annual growth rate and the exponential growth rate were determined as 0.41% and 0.39%, respectively. The urban population had a consistent growth trend, with an annual average growth rate of 2.89% and an exponential growth rate of 2.53%. In conclusion, all the variables causing Environment Degradation are highly and positively correlated with each other. An only variable showing non-significant correlation with all the other variables is "Total consumption of ODS. The repercussions of environmental degradation and the determinants of climate change are so profound that even a substantial augmentation in irrigation infrastructure or intensity cannot mitigate the detrimental impacts these phenomena have imposed on the growth of India's agricultural sector.